Sustained Biotic-Abiotic Hybrids Methanogenesis Enabled Using Metal-Free Black Phosphorus/Carbon Nitride - Hu, Andong; Fu, Tao; Ren, Guoping; Zhuang, Minghan; Yuan, Weiqi; Zhong, Sining; Zhou, Shungui (Frontiers in Microbiology, 2022)
Biotic-abiotic hybrid systems (BAHs) constructed by integrating biological methanogens with photocatalysts offer novel approaches for the effective solar-driven conversion of CO2 to CH4, providing significant inspiration for achieving carbon neutrality and alleviating the energy crisis. As metal photocatalysts would cause photocorrosion that damage microbial cells and lead to system imbalance. Therefore, exploring suitable metal-free photocatalysts is of particular importance in the search for more efficient and sustainable BAHs to improve the actual operability and applicability of the approach. Herein, black phosphorus/carbon nitride (BPCNx) as an alternative metal-free heterostructure combined with Methanosarcina barkeri (M. barkeri) to construct M. barkeri-BPCNx hybrid systems and investigated its cyclic methanogenesis performance. Our results demonstrated that the BPCNx promotes the separation of photogenerated charges and enhances the quantum yield, providing a sustained energy source for cyclically driven M. barkeri reduction of CO2 to CH4 under visible light. Our system achieved a total CH4 yield of 1087.45 ± 29.14μmol·gcat−1 after three cycles, 1.96 times higher than that of the M. barkeri-Ni@CdS. The key to achieving the cyclic stability of M. barkeri-BPCNx overcame the defects of the metal photocatalyst and kept cell permeability, effectively maintaining the activity of M. barkeri. These results highlight the viable role of BPCNx as metal-free photocatalysts in the construction of BAHs for sustained and efficient methanation of CO2, which is conducive to the development of an environmentally-friendly, low-cost, and efficient strategy for the conversion of CO2 to CH4.